A Hadith-Based Analysis of Racial Equality in Jonathan A.C. Brown’s Islam and Blackness - Budiman, Arif; Handayana, Sri (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study examines racism as explored by progressive Western Islamic scholar Jonathan A.C. Brown in his book Islam and Blackness. Racism is shaped by specific perceptions of race and blackness originating in the West, particularly in the United States, which have significantly influenced global discussions and debates. Distinctions between black and white remain stark in various social spheres. Employing qualitative research based on textual materials gathered through library research, this study utilizes a primary-source dialogue approach. The hadith analysis method applied is domain analysis, aiming to explore and analyze content. According to Brown, racial equality issues stem from varied ethnic preferences across regions, where culture plays a crucial role in shaping perceptions. The most malleable components of racial dynamics are those influenced by cultural conditioning. Within the framework of Islamic tradition, the Prophet Muhammad, as the principal advocate for justice, explicitly called for dismantling severe social boundaries in his community. Consequently, the most effective solution lies in the commitment of individuals, communities, and communal leaders to transcend racial, socioeconomic, and cultural divides. This study contributes to a deeper understanding of how Islam, as interpreted by Brown, can provide novel perspectives for combating racism and racial discrimination. It underscores the importance of integrating textual, scientific, and transformative philosophical perspectives. The research also enriches the global discourse on racial equality by connecting social and religious issues while proposing Islamic-based solutions to dismantle prevailing social barriers.